Comparison Between Ultrasonographic and Standing Magnetic Resonance Imaging Findings in the Podotrochlear Apparatus of Horses With Foot Pain - Evrard, Laurence; Joostens, Zoë; Vandersmissen, Maxime; Audigié, Fabrice; Busoni, Valeria (Frontiers in Veterinary Science, 2021)
This prospective study aimed to blindly compare the ultrasonographic and standing magnetic resonance imaging (sMRI) findings in deep digital flexor tendon (DDFT), navicular bone and navicular bursa in horses with foot pain, positive digital analgesia and without definitive radiographic diagnosis. Ultrasonography detected more DDFT abnormalities (32/34 feet versus 27/34 with sMRI) but identified less palmar navicular abnormalities (23/34 feet versus 30/34 with sMRI). In suprasesamoidean DDFT lesions, which were mainly dorsally located, changes in echogenicity did not correspond to a particular pattern of sMRI signal change. Transcuneal ultrasonography did not allow assessment of morphology and extent of distal DDFT lesions, and sporadically discriminated the affected lobe compared to sMRI. Defects of the palmar compact bone were identified with both modalities except a parasagittal defect which was only seen at sMRI.